Maisons de prêt sur gage en Chine: un visite de Chongqing - Pairault, Thierry (Anthropologica, 2022)
The reappearance of pawnshops in China is not the mere resurrection of a past gladly spurned by the Communist Vulgate. It is the result of a revival of civil society as much as an acceptation by the Chinese Government to come to terms with economic and social reality as well as a search for solutions to the dysfunctions of the bureaucratic financial system. This is why the pawnshops that we are going to visit in Chongqing present an image combining tradition and modernity, liberalism and conservatism, substitution and complementarities, prosperity and poverty.